Expression profiling of mRNA and functional network analyses of genes regulated by human papilloma virus E6 and E7 proteins in HaCaT cells - Dai, Renjinming; Tao, Ran; Li, Xiu; Shang, Tingting; Zhao, Shixian; Ren, Qingling (Frontiers in Microbiology, 2022)
HPV oncogenes E6 and E7 are essential for HPV-related cancer development. Here, we developed a cell line model using lentiviruses for transfection of the HPV16 oncogenes E6 and E7 and investigated the differences in mRNA expression during cell adhesion and chemokine secretion. Subsequently, RNA sequencing (RNA-seq) analysis was performed to explore the differences in mRNA expression. Compared to levels in the control group, 2905 differentially expressed mRNAs (1261 downregulated and 1644 upregulated) were identified in the HaCaT-HPV16E6E7 cell line. To predict the functions of these differentially expressed genes (DEGs) the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes databases were used. Protein–protein interactions were established, and the hub gene was identified based on this network. RT-qPCR was conducted to confirm the levels of 14 hub genes, which were consistent with the RNA-seq data. According to this, we found that these DEGs participate in the extracellular matrix, cell adhesion, immune control, and cancer-related signaling pathways. Currently, more and more clinicians are depending on E6/E7mRNA results to make a comprehensive judgment of cervical precancerous lesions. In this study, 14 hub genes closely related to the expression of cell adhesion ability and chemokines were tapped out in HPV16E6E7-stably expressing cell lines, which will open up new research ideas for targeting E6E7 in the treatment of HPV-related cancers.